2014
DOI: 10.1074/jbc.m114.577148
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanism of Eukaryotic Elongation Factor 2 Kinase Activation

Abstract: Background: Eukaryotic elongation factor 2 kinase (eEF-2K) regulates protein translation elongation rates. Results: eEF-2K activation involves a two-step process of calmodulin binding and rapid Thr-348 autophosphorylation. Conclusion: Activation of eEF-2K involves two distinct allosteric steps, both of which potentially induce a conformational change. Significance: This mechanism provides a framework for understanding how eEF-2K integrates inputs from multiple upstream signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 60 publications
2
67
0
Order By: Relevance
“…Cell-based assays utilizing knockout MCF-10A (eEF-2K −/− ) cells (Sigma-Aldrich) were transfected with vectors encoding wild-type eEF-2K or the W85S mutant and lysed cells were analyzed by Western blotting using eEF-2K, eEF-2 or pT56-eEF-2 specific antibodies (Tavares et al, 2014). Details are provided in the Supplemental Experimental Procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-based assays utilizing knockout MCF-10A (eEF-2K −/− ) cells (Sigma-Aldrich) were transfected with vectors encoding wild-type eEF-2K or the W85S mutant and lysed cells were analyzed by Western blotting using eEF-2K, eEF-2 or pT56-eEF-2 specific antibodies (Tavares et al, 2014). Details are provided in the Supplemental Experimental Procedures.…”
Section: Methodsmentioning
confidence: 99%
“…al demonstrated that eEF-2K is activated through a unique two-step process initiated by the binding of Ca 2+ -loaded calmodulin (CaM) (Tavares et al, 2014). This mode of activation does not appear to occur through a “release of inhibition” mechanism (Soderling and Stull, 2001; Swulius and Waxham, 2008) and sets eEF-2K apart from other CaM-dependent kinases.…”
Section: Introductionmentioning
confidence: 99%
“…This site can even be phosphorylated in E coli, which lacks CaM, suggesting that the activity of eEF2K in autophosphorylation is not strictly Ca/CaM dependent [13] . However, it is stimulated by Ca/CaM [13,14] . The conformational change associated with the phosphorylation of Thr-348 enhances eEF2K activity by increasing its affinity for a (peptide) substrate and its intrinsic catalytic activity.…”
Section: Overview Of the Structure And Control Of Eef2kmentioning
confidence: 99%
“…Two important elongation regulatory factors are eukaryotic elongation factor 2 (eEF2) and its kinase, eEF2K. Eukaryotic elongation factor 2 kinase (eEF2K) is a Ca 2+ /calmodulin (CaM)-dependent kinase, which negatively modulates protein synthesis by phosphorylating eEF2 (Kenney et al, 2014; Tavares et al, 2014). Phosphorylation at Thr56 within the GTP-binding domain of eEF2 prevents its recruitment to ribosomes and thus blocks elongation (Carlberg et al, 1990).…”
Section: Introductionmentioning
confidence: 99%